Prevention of the development of diastasis of the wound edges during two-stage breast reconstruction - A. Kh. Ismagilov; I. F. Kamaletdinov; A. M. Akhmetzyanov; V. S. Dobrov; A. R. Gabdrakhmanova (ABV-press, 2024)
The main problem of breast reconstruction after a mastectomy is the complete destruction of all structural elements of the breast and the lack of integumentary tissues that do not allow carrying out one-stage breast reconstruction. To solve this problem, usually performing a two-stage reconstruction, which today is the most commonly used method of breast reconstruction. The peculiarity of this method is that after removal of the expander, during the second stage of reconstruction, some retraction of the skin and a decrease in the area of the prepared skin cover are observed. Thus, after installing a permanent implant and suturing the surgical wound, the skin sheath is tightened around the installed endoprosthesis, while the greater the retraction of the skin, the more pronounced the tension appears and, accordingly, the load on the sutured wound increases. As a result, the risks of developing diastasis of the wound edges with the exposure of the endoprosthesis increase, which leads to the need to remove the implant. Therefore, when carrying out the second stage of breast reconstruction, a very important moment of the operation is the suturing of the postoperative wound, the competent implementation of which allows the prevention of implant extrusion.